2020
DOI: 10.1111/cob.12430
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent and continuous energy restriction result in similar weight loss, weight loss maintenance, and body composition changes in a 6 month randomized pilot study

Abstract: Summary Poor adherence is a barrier to successful weight control. Intermittent energy restriction (IER) provides an alternative approach to those for whom daily energy restriction is not ideal. This study assessed changes in weight, body composition, and macronutrient intake for an IER and a continuous energy restriction (CONT) approach within a multicomponent weight management intervention. We randomized 35 adults with overweight/obesity (BMI = 31.2 ± 2.4 kg/m2) to CONT or IER for 24 weeks (12‐week weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 49 publications
(69 reference statements)
0
25
0
1
Order By: Relevance
“…One study 13 from a previous report was added to the remaining 25 records. 14 - 38 Among the selected 26 articles, one trial with patients with type 1 diabetes mellitus 23 reported most of the targeted outcomes as medians and ranges without variances; therefore, we excluded it from our calculation of integrated mean differences (MDs) because of the unfeasibility of calculating the standard deviation (SD) from the given data. In the end, we included 16 RCTs from 25 articles comprising 1,438 participants in this meta-analysis ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…One study 13 from a previous report was added to the remaining 25 records. 14 - 38 Among the selected 26 articles, one trial with patients with type 1 diabetes mellitus 23 reported most of the targeted outcomes as medians and ranges without variances; therefore, we excluded it from our calculation of integrated mean differences (MDs) because of the unfeasibility of calculating the standard deviation (SD) from the given data. In the end, we included 16 RCTs from 25 articles comprising 1,438 participants in this meta-analysis ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…CER is a diet strategy of reducing 15–40% of the baseline calorie needs for a continuous period for weight loss [ 18 ]. Since the appearance of IER after CER, there has been increasing controversy about the effects of IER and CER among adults with overweight or obesity on weight loss, waist circumference, and body composition [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the duration of the intervention (short term [4-12 weeks] or long term [24-102 weeks]), weight loss with ADF and 5:2 fasting was comparable to that achieved by calorie restriction (CR). 10,14,15,[25][26][27][28][29][30][31][32][33][34] Meanwhile, weight loss with TRE alone (1%-5% decrease from baseline over 8-12 weeks) 23,35,36 was not superior to that achieved with CR and was less than that observed with ADF or 5:2 fasting unless total calorie intake was restricted along with TRE. Thus, long-term TRE combined with an appropriate energy-restricted diet can enhance weight loss, but this is mainly attributed to CR.…”
Section: Time-restricted Eating (Tre)mentioning
confidence: 84%